Ideology and News Coverage in North Korea. - Ok, Chang Bong; Han, Hyeyoung (My University, 2009)
The media in North Karea are closely tied to ther communist sociopolitical structures. Therefore, news in North Korea has always been shown at the representation of the political ideology and interest of the communist party. Using a controversial foreign policy issute, named the "Six-party talks" on North Korean issues, thsi study examines whether dominant ideology has been used in their news editorials as a means to channel each political ideology into the society.
Color poster with text and tables describing research conducted by Chang Bong Ok and Hyeyoung Han, advised by Won Yong Jang.
Keywords: Ideology--Korea (North); Communism--Korea (North)--Influence; Government and the press--Korea (North); Press and politics--Korea (North); Press and propaganda--Korea (North); Posters